Comparative higher education research in times of globalisation of higher education: Theoretical and methodological insights. (July 2022) - Hauptman Komotar, Maruša
In times of globalisation of higher education, alternative theoretical and methodological approaches were introduced in the field of comparative higher education research. To stimulate the debate on this issue, this paper firstly addresses them theoretically by combining the concept of institutional isomorphism and the 'glonacal' analytical heuristic. On this basis, it discusses arguments in favour of convergence and diversity from the perspective of the internationalisation of higher education and also points to the limits of institutional isomorphism resulting from 'glonacal' influences of agencies and agency on the development of (internationalisation of) higher education. Secondly, the paper also draws attention to the influence of globalisation on the selection of methodology in comparative higher education research by exposing the limits of methodological nationalism. Along these lines, it portrays the reversed pyramid model of different horizontal and vertical levels of comparisons with which it establishes the (missing) link between the selected theoretical and methodological framework of comparative (higher education) research. In conclusion, it acknowledges the need to integrate the contextual element into the comparative framework which allows thorough analysis of complex relationships between globalisation and higher education both theoretically and methodologically.